AN INVESTIGATION OF RELATIONSHIP BETWEEN TRUNK AND LOWER EXTREMITY MUSCLE STRENGTH AND FUNCTIONAL ACTIVITY IN CHILDREN WITH SPASTIC CEREBRAL PALSY - Deger, Unal; Mutlu, Akmer (Turkey Assoc Physiotherapists, 2020)
Purpose: Muscle weakness is an motor important impairment among children with cerebral palsy (CP). This study investigated the correlation between trunk and lower extremity isometric muscle strength and functional activity in children with ambulatory spastic CP. Methods: Fifty-four ambulatory children with spastic CP, aged 7-18 years (age=12.53 +/- 3.27 years) were included in this study. Hand dynamometer was used to determine trunk flexor and extansor and lower extremity muscles (hip flexos, extansor, abductor, and adductor, knee flexor and extansor, ankle dorsiflexor and plantarflexor muscles) isometric muscle strength. Gross motor function measured using Gross Motor Function Measure (GMFM) dimensions D and E, and Gross Motor Function Classification System (GMFCS) was used to classified gross motor function level. timed up and go test (TUG) and sit to stand test (SST) were used for the evaluation of functional activity. Results: The GMFM D and E scores were significantly related to hip flexor, extansor, abductor and adductor, knee extansor and flexor, ankle dorsiflexor, and plantar flexor muscle strength (p<0.05). The TUG test was significantly associated with hip extansor and abductor, knee extansor and ankle plantar flexor muscle strength (p<0.05). The SST was significantly correlated with hip extansor and abductor, knee extansor and ankle plantar flexor muscle strength (p<0.05). Conclusion: This study showed that there is a relationship between muscle strength of the trunk and lower extremity muscle strength in children with CP and functional activity at different levels, severity, and direction. Muscle strength might play critical role in functional activities in children with CP.
Keywords: Child; Muscle Strength; Cerebral Palsy